Enzymatic Hydrolysis And Lactic Acid Bacteria Fermentation Of Okara - Adilla Mahmud, Nur (Pusat Pengajian Teknologi Industri, 2020)
The production of soybean products has been increasing throughout the world and there has been a corresponding increase in the quantity of soybean curd residue or okara being thrown out. The dumping of okara has become a problem to be solved due to its contamination to the environment. Okara is rich in fiber, fat, protein, vitamins and trace elements. Okara has potential for value-added processing and utilization which simultaneously hold the promise of increased economic benefit as well as decreased pollution potential for the environment. In this study, the optimum condition for enzymatic hydrolysis of okara on release of sugar was studied and the total protein content of okara after fermentation by lactic acid bacteria (LAB) was investigated. The optimization of enzymatic hydrolysis by viscozyme was performed using R analysis in response surface methodology (RSM) with three factors which are enzyme concentration, pH and temperature to obtain maximum sugar content as response. Based on the optimization result, the optimal condition for enzymatic hydrolysis were 4.8 % (v/w), 5.5 and 27 °C of enzyme concentration, pH and temperature respectively with the response of 1000.222 μg/mL of sugar content. The fermentation of okara was carried out by Lactobacillus plantarum by shake flask fermentation for 72 hours. After fermentation, the cell viabilty of the cell was observed. The protein content obtained after fermentation was at 33.3 % which are significantly increased before fermentation. The sugar composition after fermentation are glucose, sucrose and fructose were obtained at 0.18 mg/mL, 0.15 mg/mL and 0.004 mg/mL respectively.